1995
DOI: 10.1111/j.1460-9568.1995.tb01091.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of AMPA‐induced Lesions of the Medial Septum and Vertical Limb Nucleus of the Diagonal Band of Broca on Spatial Delayed Non‐matching to Sample and Spatial Learning in the Water Maze

Abstract: These experiments investigated in the rat the impact on spatial delayed non-matching to sample and on acquisition of the Morris water maze of (i) AMPA-induced lesions of the medial septal nucleus, which produced a marked reduction of hippocampal choline acetyltransferase activity and acetylcholine levels (measured using in vivo dialysis) together with lesser reductions in cholinergic markers in the cingulate cortex and (ii) similar AMPA-induced lesions of the vertical limb nucleus of the diagonal band of Broca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…The baseline accuracy of delayed matching and nonmatching behavior in the present study was comparable to the performance of rats in other DMTP and DNMTP studies that involved retractable levers (e.g., Bushnell 1988; Harper et al 2006) or illuminable nose-poke holes (Etherington et al 1987; McAlonan et al 1995). Treatment with amnestic drugs produced dose-dependent decreases in accuracy that were comparable to those seen in previous studies with scopolamine (Bushnell 1990; Chudasama and Muir 1997; Dunnett 1985) or THC (Mallet and Beninger 1998; Hampson and Deadwyler 2000; Heyser et al 1993).…”
Section: Discussionsupporting
confidence: 84%
“…The baseline accuracy of delayed matching and nonmatching behavior in the present study was comparable to the performance of rats in other DMTP and DNMTP studies that involved retractable levers (e.g., Bushnell 1988; Harper et al 2006) or illuminable nose-poke holes (Etherington et al 1987; McAlonan et al 1995). Treatment with amnestic drugs produced dose-dependent decreases in accuracy that were comparable to those seen in previous studies with scopolamine (Bushnell 1990; Chudasama and Muir 1997; Dunnett 1985) or THC (Mallet and Beninger 1998; Hampson and Deadwyler 2000; Heyser et al 1993).…”
Section: Discussionsupporting
confidence: 84%
“…Such behaviour might reflect a deficit of non-mnemonic processes, possibly of attention or exploration strategies. Concerning attention, different authors suggested that spatial perturbations induced by septal lesions may reflect deficits of attention processes rather than a pure memory deficiency (McAlonan et al 1995;Brandner and Schenk 1998). In addition, 8-OH-DPAT administered systemically was shown to reduce performance in tasks assessing attention processes (Carli and Samanin 2000;Nakamura and Kurasawa 2000).…”
Section: Cognitive Effectsmentioning
confidence: 98%
“…"Delayed nonmatching to position" models of short-term, spatial working memory, in which rats choose between spatially separated, retractable levers, are dependent upon the operation of cholinergic mechanisms in the hippocampus and FCX (McAlonan et al, 1995;Herremans et al, 1996). Although it has been questioned whether mnemonic (compared with motor) factors underlie the perturbation of performance in this model provoked by activation of hippocampal 5-HT 1A receptors, stimulation of 5-HT 1A autoreceptors specifically improves cognitive function (Cole et al, 1994;Porsolt et al, 1995;Stanhope et al, 1995;Warburton et al, 1997;Pache et al, 2003).…”
Section: Downloaded Frommentioning
confidence: 99%